Long-term intraocular pressure changes after intravitreal injection of bevacizumab. (1st October 2016) - Baek, Sung Uk; Park, In Won; Suh, Wool
Abstract: Purpose : To assess the long-term intraocular pressure (IOP) changes after the intravitreal injection of bevacizumab (Avastin; Genentech, Inc., South San Francisco, CA) for treatment of age-related macular degeneration (AMD) and diabetic macular edema (DME) patients and evaluate the correlation factors. Material and methods : Patients with neovascular AMD or DME underwent treat-and-extended anti-VEGF regimen in one eye and followed more than 12 months were enrolled in this study. We set three criteria of IOP elevation: (1) the IOP of the treated eye increased above the contralateral eye for at least two consecutive visits; (2) the IOP of the treated eye increased above the pre-injection IOP for at least two consecutive visits; (3) and the IOP of the treated eye increased more than 5 mmHg above the baseline IOP for at least two consecutive visits. We used mixed model univariate and multivariate analysis to assess the association between IOP elevation and independent parameters including age, sex, lens status, the number of injections, and underlying disease. Results : In total 152 patients, 83 patients with AMD and 69 patients with DME, were included in this study. Mean follow-up time was 18.7 months, with a maximum of 50 months. In IOP elevation, 54 eyes (35.6%) showed an IOP increase above that of the contralateral eye (criteria 1), 50 eyes (33.4%) showed an IOP increase above the baseline IOP (criteria 2), and an IOP increase greater than 5 mmHg above the baseline IOP observed in nine eyes (5.9%) (criteria 3). In the univariate analysis, lens status and total number of injections were statistically significant for criteria 2 and 3 (all p s < 0.05). However, in the multivariable analysis, only the number of intravitreal injections was statistically correlated with sustained IOP elevation for criteria 2 and 3 ( p < 0.001 and p = 0.039, respectively). Conclusions : Our results suggest that under long-term monitoring, with a treat-and-extended regimen, intravitreal bevacizumab injections were associated with sustained IOP elevation. In particular, multiple intravitreal injections could be associated with sustained IOP elevation.